Analysis of the Impact of Insecurity on Youth Unemployment (1990-2020): Analysis of the Impact of Insecurity on Youth Unemployment - Musa, Ibrahim (CV Putra Publisher, 2024)
Using the ordinary least square estimation technique (OLS), this research examines the impact of insecurity on youth unemployment in Nigeria between 1990 and 2020. The study focuses on the relationship between the dependent variable, unemployment (UNE), and two independent variables, the National Terrorism Index (NTI) and Crime Rate (CR). The results reveal that NTI has a positive and statistically significant effect on UNE. Specifically, a unit increase in NTI leads to a 0.000827 rise in unemployment. Additionally, Nigerian CR demonstrates a significant and positive influence on UNE, with an increase in CR resulting in a 0.005653 increase in unemployment. Given that heightened insecurity directly contributes to unemployment, the study proposes several policy recommendations. Firstly, the government should consider reducing interest rates in commercial banks to enhance the availability of loans for small business owners, enabling them to hire more employees. Furthermore, addressing corruption in both public and private sectors, combating kidnappings, and establishing additional skill acquisition centers are crucial measures to tackle the issue of insecurity and promote employment opportunities.